Quality Of Pe Buck Sperm Stored In Different Packaging - Pangestu, M; Soenarjo, CH; Siswadi, Rachmawati W; Sugiyatno, Sugiyatno; Tagama, Taswin R; Saleh, Dadang M; Haryati, Haryati; Sutarmo, Sutarmo; Setyawati, SJA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
AI for cattle has been develop in Indonesia in contrast, AI for small ruminants (sheep and goat) are less developed. Its due to the lack of facilities, processing and packaging during storage. This research aims to compare the effectivity and efficiency of two different packaging technique (test tube and straw). Test tube and 0.25 ml mini straw were tested . Semen was obtained from adult PE buck (3 yr) after collection by using artificial vagina. The fresh semen was then evaluated and diluted 5 folds with 2.9 percent Na-citrate. Diluted semen then packed in test tube and mini straw, and stored in refrigerator (100C) for 7 days. Observations were done everyday on sperm motility, abnormality and percentage of live sperm. Observation were made at 370C. Observation on fresh ejaculate showed that semen has 6x 109/ml concentration, 90 percent motility, 8 percent abnormality and 95 percent live sperm. Five folds dilution reduced sperm concentration to 1.2 x 109/ml, but did not change sperm motility, abnormality and percent of live sperm. Sperm was then packed according to the treatments. Storage in both packaging did significantly reduce (P<0.01) sperm motility and percent live sperm, but not for sperm abnormality. All sperm stored in test tube were classified death at day 5 storage. However, sperm in the straw were remain live eventhough the percentages was low. It can be concluded that straw has a better result than test tube. Eventhough sperm motility was extremely low, it remains valuable for cervical insemination. (Animal Production 1(1) : 24-29 (1999). Key Words : Sperm, PE Buck, Straw, Test Tube